Multivariate comparison of craniofacial morphology in different types of facial clefts - Smahel, Z; Hradiský, D; Müllerová, Z (Acta chirurgiae plasticae, 1999)
Based on X-ray measurements of the head of 187 adult men with cleft lip and/or palate, the authors compared, using the multivariate method, deviations in the craniofacial morphology between different types of clefts in the following seven groups: cleft lip alone, complete and incomplete isolated cleft palate, cleft of the soft palate only, unilateral complete and incomplete and bilateral complete cleft lip and palate. The X-ray films were evaluated according to Jarabak's method. A special position is held by cleft lip alone with minimal skeletal and dental effects. Isolated clefts of the palate display in skeletal analysis the same basic deviations as clefts of the lip and palate; in dental analysis the deviations are smaller (in particular there is no retroinclination of the upper incisors). The effect is much milder in isolated clefts of the soft palate. In cleft lip and palate there is, in contrast to isolated clefts of the palate, retrusion of the mandible; in bilateral clefts, in conjunction with persisting protrusion of the premaxilla the depth of the upper jaw is not reduced, the facial skeleton is not flattened and the sagittal intermaxillary relations are not impaired. In the basic developmental pattern there is, however, no difference between different types of clefts which affect the palate (probably in conjunction with postoperative sequelae). The variable which differentiates most types of clefts in the skeletal analysis is the depth of the maxilla; in the dental analysis it is the interincisal angle, which is, however, influenced by treatment. Jarabak's analysis can record the basic deviations of the configuration of the bony face with a cleft but does not detect some important characteristics such as the vertical proportionality of the face and the posteroposition of the maxilla. The assessment of the soft profile is, however, inadequate and unsuitable.
Keywords: Maxilla; Mandible; řezáky; Cleft Lip; Humans; Lip; kefalometrie; Multivariate Analysis; Cephalometry; obličej; analýza rozptylu; dospělí; Analysis of Variance; lidé; Palate, Soft; Incisor; obličejové kosti; Adult; Vertical Dimension; multivariační analýza; Male; ret; patro měkké; Cleft Palate; rozštěp patra; rozštěp rtu; mandibula; Face; mužské pohlaví; zubní okluze; Dental Occlusion; mezičelistní vztahy; maxila; Facial Bones